Digital Financial Transformation in Indonesia: Non-Cash Usage Via Modified UTAUT2 With Trust - Setio Ardy Nuswantoro; Muhammad Ulfi; Sahwari Sahwari; Linda Linda; Amara Damayanti (Universitas Ahmad Dahlan, 2024)
Digital payments are transforming the financial landscape in Indonesia, offering fast and efficient services that meet the growing demand for cashless transactions. This study analyzes the factors influencing digital payment adoption using the UTAUT2 model, with the addition of Trust as a critical factor. Cluster analysis was also conducted using the k-prototype algorithm to see their characteristics and perceptions about digital payments. A survey was conducted from June to August 2024, gathering 451 responses from users of digital payment services. The data were analyzed using structural equation modeling to test 13 hypotheses. Of these, 10 hypotheses were accepted, indicating that Effort Expectancy, Performance Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Habit, and Trust significantly influence Behavioral Intention. Social Influence and Facilitating Conditions also directly impacted trust, which further strengthened users' intention to adopt digital payments. However, Price Value did not significantly affect Behavioral Intention, and Habit was not a strong predictor of continued use behavior. Trust emerged as a key factor in driving user engagement and long-term adoption. The study highlights that while convenience and social influence are crucial, trust in digital payment services is essential for sustaining user adoption. Cluster analysis divides respondents into four clusters, where the first, second, and third clusters are from young people with different perceptions about digital payment and the fourth cluster is from mature people who are mostly working as teachers or lecturers. These findings offer valuable insights into promoting digital payment usage and supporting Indonesia’s shift towards a digital economy.